Performance perspectives a critical introduction - Pitches, Jonathan 1968-; Popat, Sita (Palgrave Macmillan, 2011)
This critical introduction to Performance Studies provides undergraduates with an accessible way into terminology and context. Using a tripartite structure that combines the voices of artists, critics and teachers, it addresses a variety of practices moving through body, space, time, technology, interactivity and organization.